Analisis Ekonomi Syariah Terhadap Kearifan Lokal Mula Balu Sebagai Penglaris Di Pasar Sentral Sengkang - Risman Rusanda; Syahriyah Semaun; Islamul Haq; Sitti Jamilah Amin; Andi Bahri S (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
The purpose of this study is to describe the understanding of traders in the Sengkang central market Wajo Regency, towards the practice of local wisdom Mula Balu as a sales booster in sharia economic analysis. The results of this empirical qualitative study are: 1) Traders' understanding of the concept of Mula Balu as something positive and not contrary to religion because it is not obtained from shamanic practices but is obtained from the process of learning sharia, tarekat, hakikat and ma'rifatullah and is understood as a manifestation of prayer or Assennung-sennungeng ri decenge (hope for goodness). 2) The practice is very diverse, some use mantras such as Arase Kursia, folded (Rekko ota) and stored normally. 3) Sharia economic analysis of the use of Mula Balu as a sales booster in the Sengkang central market, Wajo Regency shows three results of the analysis.